Microvessel Density in Patients with Cutaneous Melanoma: An Up-to-Date Systematic Review and Meta-Analysis - Konstantinos Perivoliotis; Panagiotis Ntellas; Katerina Dadouli; Prodromos Koutoukoglou; Maria Ioannou; Konstantinos Tepetes (Journal of Skin Cancer)
Background. We conducted a meta-analysis, in order to appraise the effect of microvessel density (MVD) on the survival of patients with cutaneous melanoma. Methods. This study was conducted according to the PRISMA guidelines and the Cochrane Handbook for Systematic Reviews of Interventions. A systematic literature search in electronic databases (MEDLINE, Web of Science, and Cochrane Central Register of Controlled Clinical Trials) was performed. Fixed Effects or Random Effects model was used, based on the Cochran Q test. Results. In total 9 studies (903 patients) were included. Pooled HR for overall survival (OS) and disease-free survival (DFS) were 2.62 (95% CI: 0.71–9.60, p=0.15) and 2.64 (95% CI: 0.82–8.47, p=0.10), respectively. Odds ratios of overall survival between high and low MVD groups, at 12 (1.45, 95% CI: 0.16–13.24), 36 (2.93, 95% CI: 0.63–13.59), and 60 (4.09, 95% CI: 0.85–19.77) months did not reach statistical significance. Significant superiority of low MVD group, in terms of DFS, at all time intervals (OR: 4.69, p<0.0001; OR: 2.18, p=0.004; OR: 7.46, p=0.01, resp.) was documented. Discussion. MVD does not affect the HR of OS and DFS. A strong correlation with DFS rates at 12, 36, and 60 months was recorded.